Conocimientos de las madres adolescentes sobre el cuidado del recién nacido en el Servicio de Gineco-Obstetricia del Hospital Isidro Ayora 2014 - Pullaguari Maza, Jenny Soledad (2015)
The teen pregnancy still it remains one of the main factors contributing to maternal and infant mortality, is considered the second leading cause of maternal death worldwide in women aged 15 to 19 years, added to this mortality risk prenatal record and the likelihood of low birth or death in the first weeks of life weight. The research called: Knowledge of adolescent mothers on newborn care in the service of Gynecology and Obstetrics of Isidro Ayora Hospital, is a work of descriptive type since it allowed to measure the aspects of the phenomenon to investigate, the sample was constituted by 35 teen mothers of between 13 to 19 years of age, the used technology was the survey; the instrument a questionnaire, the same one that was applied by the purpose of valuing the knowledge. The obtained results determined that they know mothers' great part that the mother lactation must be a sole right during this stage, and the advantages of the lactation for his son, with regard to the hygiene; the bath of the newborn child must be a diary and have a minor duration to ten minutes, more than forty certainly about mothers it knows on this aspect. n hygiene of the umbilical cord and identification of signs of alarm; fifty per cent knows the suitable technology, more than sixty per cent knows on frequency and eighty per cent they know on signs of alarm of the umbilical cord. On prevention of accidents, it exists a great percentage of teen mothers who do not know on the measures in addition know some aspects on tactile and auditory stimulation and a great percentage he does not know on signs of alarm of the newborn child, since only it knows the fever, respiratory difficulty as the principal ones. KEYWORDS Taken care of the newborn child; prevention of accidents; signs of alarm; early stimulation.